Investigation of the Effects of Two Different Biopolymers on the Strength Parameters of Silty Soil - Kara, Halil Oğuzhan; Yilmazoğlu, Mehmet Uğur (Gazi Universitesi Fen Bilimleri Dergisi Part C: Tasarim ve Teknoloji, 2025)
Soil improvement methods are commonly employed to enhance the load-bearing capacity of weak soils. Due to environmental concerns, traditional additives like lime and cement are increasingly being replaced by more sustainable alternatives. Recently, biopolymers have gained attention as environmentally friendly options for soil stabilization. However, combining biopolymers with additional agents to enhance bond strength is rare. This study investigates the effects of using Guar Gum and Xanthan Gum biopolymers in combination with Calcium Chloride (CaCl₂) on the strength parameters of silty soil. Biopolymers are known to form gel-like structures between soil particles, increasing strength. At the same time, Calcium Chloride interacts with the carboxyl groups of biopolymers, creating cross-linkages that further improve soil strength. In this research, biopolymers and Calcium Chloride were combined with silty soil and subjected to 7,28,56 and 90 days of curing. Unconfined compressive strength (UCS) and direct shear tests were conducted, and the results were compared with reference samples. Changes in internal friction angle and cohesion were also analyzed based on different biopolymer ratios. The results demonstrated significant improvements in the strength of long-term cured samples, with Calcium Chloride enhancing the cross-linking effect of biopolymers. These findings suggest that biopolymers, in combination with Calcium Chloride, can be effective in environmentally friendly soil stabilization projects.